Helicobacter acinonyx sp. nov., Isolated from Cheetahs with Gastritis - Eaton, K. A.; Dewhirst, F. E.; Radin, M. J.; Fox, J. G.; Paster, B. J.; Krakowka, S.; Morgan, D. R. (International Journal of Systematic and Evolutionary Microbiology, 1993)
Four strains of a novel Helicobacter species were isolated from the stomachs of cheetahs (Acinonyx jubilatus ) with gastritis. These isolates were phenotypically similar to Helicobacter pylori. The isolates were gram-negative, spiral bacteria which grew under microaerophilic conditions at 37°C, but not at 25 or 42°C, and produced urease, catalase, oxidase, alkaline phosphatase, and gamma-glutamyl transpeptidase. The isolates did not ferment glucose, mannitol, inositol, sorbitol, rhamnose, sucrose, melibiose, amygdalin, or arabinose; hydrolyze hippurate or indoxyl acetate; or reduce nitrate. They did not produce H2S from triple sugar iron agar, and they did not grow in the presence of 1.0% glycine or 1.5% NaCl. They were resistant to nalidixic acid and sensitive to cephalothin and metronidazole. Cells were typically 0.3 by 2.0 μm and possessed tufts of two to five sheathed, monopolar flagella. The G+C content of strain 90-119 was 30 mol%. Cluster analysis of densitometry scans of polyacrylamide protein gels revealed more than 70% similarity of the cheetah isolates to H. pylori, less than 60% similarity to Helicobacter fells, and less than 50% similarity to Helicobacter mustelae. Complete 16S rRNA sequences were determined for two of the cheetah isolates. Phylogenetic analysis was performed by comparing the cheetah sequences to those of 19 reference strains, inluding H. pylori, H. felis (two strains), H. mustelae, Helicobacter muridarum, “Flexispira rappini,” Wolinella succinogenes, Campylobacter coli, Campylobacter concisus, Campylobacter curvus, Campylobacter fetus, Campylobacter hyointestinalis, Campylobacter jejuni, Campylobacter lari, Campylobacter rectus, Campylobacter sputorum subsp. bubulus, a Campylobacter sp. (pig isolate), [Bacteroides] gracilis, and [Bacteroides] ureofyticus. The 16S rRNA sequences for 13 of the 19 reference species have not previously been reported. Phylogenetic analysis demonstrated that the cheetah isolates were most closely related to H. pylori (97.4% similarity), H. felis (96.1% similarity), and H. mustelae (93.4% similarity). On the basis of these findings, we propose that these isolates represents a novel species of Helicobacter, which we designate Helicobacter acinonyx. The type strain is 90-119 (CCUG 29263, ATCC 51101).